Improving quantum microscopy and lithography via Raman photon pairs: II. analysis - Scully, M.O.; Ooi, Chong Heng Raymond (2004)
We show that by using the strongly correlated photon pairs generated in a Raman quantum erasure scheme (Scully M and Druhl K 1982 Phys. Rev. A 25 2208), it is possible to exceed the Rayleigh resolution limit of classical microscopy. The complete analysis of the underlying physics is given here. Further discussion of the physics and potential applications are presented in a companion paper (Scully M O 2004 Improving quantum microscopy and lithography via Raman photon pairs: I. Biological applications, submitted).